Two previously unknown Phytophthora species associated with brown rot of Pomelo (Citrus grandis) fruits in Vietnam - Puglisi, Ivana; De Patrizio, Alessandro; Schena, Leonardo; Jung, Thomas; Evoli, Maria; Pane, Antonella; Van Hoa, Nguyen; Van Tri, Mai; Wright, Sandra; Ramstedt, Mauritz; Olsson, Christer; Faedda, Roberto; et al. (PloS one, 2017)
Two distinct Phytophthora taxa were found to be associated with brown rot of pomelo (Citrus grandis), a new disease of this ancestral Citrus species, in the Vinh Long province, Mekong River Delta area, southern Vietnam. On the basis of morphological characters and using the ITS1-5.8S-ITS2 region of the rDNA and the cytochrome oxidase subunit 1 (COI) as barcode genes, one of the two taxa was provisionally named as Phytophthora sp. prodigiosa, being closely related to but distinct from P. insolita, a species in Phytophthora Clade 9, while the other one, was closely related to but distinct from the Clade 2 species P. meadii and was informally designated as Phytophthora sp. mekongensis. Isolates of P. sp. prodigiosa and P. sp. mekongensis were also obtained from necrotic fibrous roots of Volkamer lemon (C. volkameriana) rootstocks grafted with 'King' mandarin (Citrus nobilis) and from trees of pomelo, respectively, in other provinces of the Mekong River Delta, indicating a widespread occurrence of both Phytophthora species in this citrus-growing area. Koch's postulates were fulfilled via pathogenicity tests on fruits of various Citrus species, including pomelo, grapefruit (Citrus x paradisi), sweet orange (Citrus x sinensis) and bergamot (Citrus x bergamia) as well as on the rootstock of 2-year-old trees of pomelo and sweet orange on 'Carrizo' citrange (C. sinensis 'Washington Navel' x Poncirus trifoliata). This is the first report of a Phytophthora species from Clade 2 other than P. citricola and P. citrophthora as causal agent of fruit brown rot of Citrus worldwide and the first report of P. insolita complex in Vietnam. Results indicate that likely Vietnam is still an unexplored reservoir of Phytophthora diversity.
Keywords: nemoci rostlin; DNA fungální; kořeny rostlin; Vietnam; Phylogeny; Plant Roots; Sequence Analysis, DNA; sekvenční analýza DNA; Plant Diseases; DNA, Fungal; Fruit; ovoce; Phytophthora; fylogeneze; Citrus